A Consultation-Liaison Psychiatry Approach to Anxiety in a Patient with Multidrug-Resistant Tuberculosis: Case Report - Hapsari, Septika Purnastuti; Nugroho, Nur Prasetyo; Rahmawati, Novi Agung (Universitas Ahmad Dahlan, 2026)
The interplay of social stigma, the grueling duration of treatment, and residual drug toxicities frequently triggers psychiatric comorbidities in multidrug-resistant TB (MDR-TB), which can severely compromise treatment adherence. We reported a 24-year-old female MDR-TB patient presented with escalating insomnia and severe anxiety. Her psychological distress followed the onset of physical complications three months prior, including peripheral paresthesia (tingling) and impaired mobility. These physical symptoms exacerbated her breathlessness and sleep disturbances. Following a referral to the psychiatry department, a Consultation-Liaison Psychiatry (CLP) framework was initiated. Through integrated psychiatric intervention and pharmacological dose adjustment for her MDR-TB regimen, the patient’s anxiety significantly diminished, and her physical side effects became manageable. The following evaluation of MDR-TB, both clinically and radiologically, showed improvement. The patient declared cured after a six-month duration of MDR-TB treatment. CLP provides a vital bridge in specialized care, addressing the depression, anxiety, and psychosis that often act as barriers to successful MDR-TB recovery.